Dr. Darina Oravcová — Deep Plane Facelift — Poprad - Oravcová, Darina (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Darina Oravcová, practicing in Poprad, Slovakia. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003217; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; slovakia; poprad